The session structure as a potentiating element of learning and training in collective sports from the perspective of non-linear pedagogy - Martín Barrero, A.; Camacho Lazarraga, P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
In recent years, new methodological trends have emerged with force, establishing as one of the important elements the manipulation of constraints, in which certain behaviors are made possible in order to facilitate meaningful learning. However, these levels of constraints are not the only ones that can be conditioned to favor learning, since the learning context is made up of more pieces. This work aims to propose the structure of the session as a level of constraint that enables learning. An intervention was carried out with soccer players (n=24) of the U13 category of a professional club, during 3 sessions with different conditioned tasks. The results indicate that, in general terms, the adequate ordering of tasks during the session helps to favor the transfer of the knowledge acquired, concluding that the structure of the session could be considered as a level of constraint.